2022
DOI: 10.1002/hep4.1911
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Human Endothelial Cells Into Liver Cancer‐Forming Cells Using Nonintegrative Episomal Vectors

Abstract: Liver cancer is an aggressive cancer associated with a poor prognosis. Development of therapeutic strategies for liver cancer requires fundamental research using suitable experimental models. Recent progress in direct reprogramming technology has enabled the generation of many types of cells that are difficult to obtain and provide a cellular resource in experimental models of human diseases. In this study, we aimed to establish a simple one‐step method for inducing cells that can form malignant human liver tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…By contrast, recent studies have suggested that all transcription factors can act as pioneer factors depending on their expression levels and abundance ratios [ 31 , 32 ]. This idea is partially supported by other studies showing that the outcome of cellular reprogramming is influenced by the expression levels and abundance ratios of reprogramming-inducing transcription factors [ 16 , 33 , 34 ]. It has also been reported that transcription factors introduced and exogenously expressed in cells can either promote or inhibit chromatin binding to each other [ 35 ].…”
Section: Molecular Mechanisms Of Transcriptional and Chromatin Regula...mentioning
confidence: 61%
See 1 more Smart Citation
“…By contrast, recent studies have suggested that all transcription factors can act as pioneer factors depending on their expression levels and abundance ratios [ 31 , 32 ]. This idea is partially supported by other studies showing that the outcome of cellular reprogramming is influenced by the expression levels and abundance ratios of reprogramming-inducing transcription factors [ 16 , 33 , 34 ]. It has also been reported that transcription factors introduced and exogenously expressed in cells can either promote or inhibit chromatin binding to each other [ 35 ].…”
Section: Molecular Mechanisms Of Transcriptional and Chromatin Regula...mentioning
confidence: 61%
“…These directly induced stem and progenitor cells may be preferred over terminally differentiated cells because of their potential for propagation and differentiation in culture and after transplantation into injured tissues and organs. In addition, cell reprogramming technology has enabled the direct induction of tumor-forming cells from normal somatic cells [ 15 , 16 ] and has evolved to induce stable inhibition of tumor cell proliferation and functional differentiation of tumor cells using a defined set of transcription factors [ [17] , [18] , [19] ]. Direct reprogramming technology, which uses specific combinations of transcription factors, is expanding into many fields beyond regenerative medicine.…”
Section: Transcription Factor Sets Used In Direct Cellular Reprogrammingmentioning
confidence: 99%
“…Total RNA was obtained from hepatocytes freshly isolated from adult mouse livers, hepatocytes and dediHeps in monolayer cultures, dediHep aggregates, dediHep-derived SOs, FIPC-derived SOs, dediHep-derived BOs, ISC-derived BOs, CLiPs, and hepatocytes cultured with DMSO or verteporfin (0.3 µM) for 1 week after plating as described above and analyzed by 3ʹ untranslated region sequencing (CEL-seq2) [46][47][48] . Calculation of log fold-change (logFC) and identification of differentially expressed genes (FDR < 0.1, 2 < logFC) were performed by edgeR program (version 4.0.2) [49][50][51] with unique molecular identifier (UMI) count values.…”
Section: Transcriptome Analysismentioning
confidence: 99%